History and Philosophy of Science at the Crossroads of Doctoral Education’s Reforms: Polemical Notes - E. N. Ishchenko (Высшее образование в России)
The article examines the importance of the discipline of “History and Philosophy of Science” in the context of a new model for training doctoral students. The Russian universities and institutions of higher education should begin its implementation in September 2021. The author analyzes the history of the development and implementation of the course of “History and Philosophy of Science” as an academic discipline, which took place against the background of transformations in doctoral education. The article shows that the significant efforts of the professional philosophical community aimed at conceptualizing the methodological and methodical foundations of the discipline were successful and played an important role in the process of training doctoral students. The professional community not only gave an adequate response to the challenge of the educational reform, but also used it as a chance for renewal, realization of its own scientific and pedagogical potential. The transition to a new model of doctoral education, taking into account the modern realities of the knowledge society, should take into account the need to form critical thinking in postgraduate students as the most important competence. The change of focus from educational training to research component should not lead to utilitarian approach implementation aimed at purely quantitative indicators. The high quality of training future researchers, and focus on the development of human capital meet the challenges posed by the contemporary knowledge society.